Chemical Constituents and Biological Activity of Lipids, Proteins and Flavonoids of Nerium oleander L. Growing in Egypt - A. Shams, Khaled; M. Radwan, Hany; A. Tawfik, Wafaa; A. Habib, Amira; M. Abdel-Mohsen, Mona; M. Abou-Setta, Lobna (Asian Journal of Chemistry, 2011)
The lipid contents of Nerium oleander L. grown in Egypt were analyzed by GLC. A series of hydrocarbons ranging from C19-C31 in addition to cholesterol, campasterol, stigmasterol and the triterpenoid a-amyrin were identified. The GLC of the fatty alcohol fraction revealed the presence of 8 fatty alcohols represented about 88 % of the total alcohol. Also, the analysis of the fatty acid fraction revealed the presence of 11 fatty acids in which palmitic acid (27.88 %) represented the main acid. The study of the flavonoidal fraction revealed the isolation and identification of four compounds which proved to be luteolin 4’-methyl ether, luteolin-7-O-glucouronid, apigenin-7- O-galactoside and isorhamnetin-3-O-galactoside. Identification of the isolated compounds was carried out by spectroscopic analysis viz., UV, MS, NMR, TLC, PC and acid hydrolysis of the glycoside compounds. The crude protein of Nerium oleander L. was found to be 12.33 %. The analysis of the amino acids isolated from the plant using the amino acid analyzer, revealed the presence of 14 amino acids, in which alanine (15.49 %) represented the main component. The mucilage hydrolyzate of the aerial parts of the plant was found to contain rhamnose, arabinose and galactose by using PC. The radical scavenging effects of the tested extracts and isolated compounds on DPPH free radical were studied, in which fatty alcohol and fatty acid fractions showed low antioxidant activity, also n-butanol and the unsap. fractions showed moderate activity. Whereas, the four isolated flavonoidal compounds showed a strong antioxidant activity compared to Trolox (standard antioxidant compound). The different extracts and isolated compounds of the plant exhibited no cytotoxic activity against Ehrlich-ascitis carcinoma cell line at the tested concentrations.